MANFAAT MENDENGARKAN MUSIK KLASIK TERHADAP PENYESUAIAN DIRI MAHASISWA MUSIK GEREJA IAKN KUPANG DALAM MENGHADAPI PANDEMI COVID-19 - Kabnani, Jefri Soli; Novita Sheldena, Devi (Program Studi Pendidikan Musik, 2021)
At the beginning of 2020 the Indonesian people were shocked by the outbreak of a new type of virus, namely Coronavirus disease 2019 (COVID-19). The impact of the outbreak of this virus is felt by the world of education in Indonesia, especially the City of Kupang. This condition is academically alone in a student in achieving his goals, namely from a physical and psychological perspective. This impact also reported Church Music students at the State Christian Institute (IAKN) Kupang. The purpose of the study was to look empirically about the benefits of listening to classical music for students of IAKN Kupang Church Music in the face of the Covid-19 Pandemic. This study used a qualitative method by taking the subject of 8 Church Music students. Data were collected by interviewing and observing students. The results obtained were that students felt significant benefits from listening to classical music during the pandemic. Listening to classical music can affect the psychological condition of students such as feeling calmer, more comfortable, relaxed and reducing feelings of worry. In addition, it affects the physical condition of students such as heart rate, decreased blood pressure and relaxed tense muscles. The influence of academic classical music is to provide inspiration in assignments given by lecturers, so that students carry out lectures and practice.